Implementation of Inclusive Curriculum in Realizing Child-Friendly Education - Fety Dian Andriyani; Banun Hafifah C.K.; Ana Fitrotun Nisa; Akbar Al Masjid; Berliana Heru Cahayani (Journal of Psychology and Instruction, 2025)
This study aims to analyze the implementation of inclusive curriculum management at SD INTIS School Yogyakarta as an effort to realize child-friendly education. This research uses a qualitative descriptive approach with data collection methods through observation, interviews, and documentation. The results show that SD INTIS School Yogyakarta applies an inclusive curriculum model that includes curriculum duplication and modification to accommodate the diversity of student needs. The school also provides services and facilities that support the optimal development of all students. Despite facing challenges related to resources, teacher readiness, and adaptation of learning materials, SD INTIS School Yogyakarta continues to strive to develop an effective and efficient inclusive curriculum management model. The findings of this research are expected to contribute to the development of a comprehensive inclusive curriculum management model and serve as a reference for other schools.